CORPORATE GOVERNANCE: PERSPEKTIF TEORI PERUSAHAAN - Adrian Teja (Bina Ekonomi, 2003)
The main differences between corporate governance theory from the theory of the firm perspective and other perspectives, such as simple finance perspective, the stewardship perspective, the political perspective, and the stakeholder perspective, is the power of the agent The theory of the firm perspective assumes that agent has a dominant power but the other perspectives assume principal has a dominant power. The agent build information asymmetry through increasing risk and complexity of the firm. The increasing of business risk induce principal to invite other principal to spread the risk. When the stake of principal in the firm is small relative to her wealth, their incentive to monitor the agent tend to decreasing. The complexity of the firm need a lot of good monitor. Since good monitor is limited then agent will be under monitored.